Pengaruh pemberian plasma kaya trombosit dan karbonat hidroksiapatit pada proses penutupan defek tulang kepala hewan coba tikus - Nirmalasari, Lucia; Oley, Maximillian Ch.; Prasetyo, Eko; Hatibie, Mendy; Loho, Lily L. (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Recently, platelet rich plasma has been popular and its use has begin on human in developed countries. Platelet rich plasma is defined as autologus blood with concentration of platelets three to five times above baseline level, which contains at least seven growth factors like Platelet Derived Growth Factor (PDGF), Platelet Derived Angiogenesis Factor (PDAF), Platelet Derived Endothelial Growth Factor (PDEGF), Transforming Growth Factor Beta (TGF- Î²), Insulin like Growth Factor (IGF), Fibroblast Growth Factor (FGF), and Vascular Endothelial Growth Factor (VEGF). The golden standard for reconstruction of cranial bone defects demonstrates osteoconduction scaffold, osteoinduction like growth factors, and osteogenesis. Alloplastic biomaterials have revolutionalized craniofacial reconstruction. Carbonated hydroxyapatite (CHA) has been studied for years as implant material due to its similarity with the mineral component of bone. In this study we investigated and compare the effects of PRP and CHA on bone regeneration in rat cranial defects. This was an experimental study with a true experimental design on white male rats (Rattus norvegicus). Cranial deffects of 3 mm diameter were created in rat cranium and grafted with CHA and PRP combination, CHA alone, and control. The relationships among them were analyzed by using Mann Whitney and SPSS Statistics Program Package Version 22.0. The results showed that the experimental group of 2 weeks had no different between inflammatory reaction (P = 0.119), woven bone (P = 0.094) and lamellar bone (P = 0.130). At 4 weeks,a combination of PRP and CHA showed a superior growth of lamellar bone compared to CHA (P = 0.009). Conclusion: A combination of PRP and CHA in bone regeneration showed a histological tendency toward increased bone formation. However, future investigations should be conducted in different period times.Keywords: platelet rich plasma, carbonated hydroxyapatite, cranial defectAbstrak: Plasma kaya trombosit makin banyak digunakan dalam dunia kedokteran. Di negara maju pengunaannya sudah mulai diteliti pada manusia. Plasma kaya trombosit adalah fraksi plasma darah dengan konsentrasi platelet 3-5 kali diatas nilai normal yang mengandung sekurang-kurangnya 7 faktor pertumbuhan, diantaranya Platelet Derived Growth Factor (PDGF), Platelet Derived Angiogenesis Factor (PDAF), Platelet Derived Endothelial Growth Factor (PDEGF), Transforming Growth Factor Beta (TGF- Î²), Insulin like Growth Factor (IGF), Fibroblast Growth Factor (FGF), dan Vascular Endothelial Growth Factor (VEGF) yang dapat meningkatkan proses osteogenesis. Karbonat hidroksiapatit adalah material pengganti tulang yang dapat mempercepat regenerasi jaringan tulang serta memiliki kandungan kalsium,fosfat dan karbonat yang mirip dengan tulang manusia. Tulang yang tumbuh pada awal berupa tulang muda yang memiliki serat kolagen yang tidak teratur dan banyak osteosit disebut tulang imatur. Tulang imatur kemudian akan diganti oleh tulang matur yang memiliki serabut kolagen yang teratur. Jenis penelitian ini ialah eksperimental pada 36 hewan coba tikus putih wistar (Rattus norvegicus). Defek kalvaria pada tikus dengan diameter 3 mm diisi sesuai perlakuan: plasma kaya trombosit dengan karbonat hidroksiapatit, karbonat apatit tunggal, dan kontrol. Plasma kaya trombosit dibuat dari autologus darah tikus yang diberi perlakuan plasma kaya trombosit serta karbonat hidroksiapatit dan karbonat apatit tunggal. Data dianalisis dengan uji Mann Whitney dan diolah dengan SPSS. Hasil penelitian memperlihatkan pada minggu ke-2, tidak terdapat perbedaan bermakna reaksi inflamasi (P = 0,119), tulang imatur (P = 0,094), dan tulang matur (P = 0,130) diantara ketiga perlakuan. Pada minggu ke-4, tulang matur yang terbentuk lebih banyak pada perlakuan plasma kaya trombosit dan karbonat hidroksiapatit (P = 0,009). Simpulan: Pemberian plasma kaya trombosit dan karbonat hidroksiapatit dapat meningkatkan proses penutupan defek tulang kepala hewan percobaan tikus.Kata kunci : plasma kaya trombosit, karbonat hidroksiapatit, defek tulang kepala.